2015
DOI: 10.1093/molehr/gav066
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of human epididymis epithelial cells reveal the functional diversity of caput, corpus and cauda regions

Abstract: This work was supported by the National Institutes of Health: R01HD068901 (PI: A.H.). The authors declare no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(115 citation statements)
references
References 59 publications
4
95
1
Order By: Relevance
“…Attached along the caudomedial border of the testis, the epididymis can be divided into three main segments, the caput (head), corpus (body) and cauda (tail), which finally tapers into the vas deferens. It is through this tube that sperm progressively acquire functional competency for fertilisation, and therefore characteristic highly regionalised gene and protein expression profiles give rise to a dynamic intraluminal environment [14]. One particular β-defensin, (BD126) has been documented to play a number of roles critical to sperm survival, motility and interaction with the female reproductive tract and its secretions [1517].…”
Section: Introductionmentioning
confidence: 99%
“…Attached along the caudomedial border of the testis, the epididymis can be divided into three main segments, the caput (head), corpus (body) and cauda (tail), which finally tapers into the vas deferens. It is through this tube that sperm progressively acquire functional competency for fertilisation, and therefore characteristic highly regionalised gene and protein expression profiles give rise to a dynamic intraluminal environment [14]. One particular β-defensin, (BD126) has been documented to play a number of roles critical to sperm survival, motility and interaction with the female reproductive tract and its secretions [1517].…”
Section: Introductionmentioning
confidence: 99%
“…Many functional pathways in the human epididymis show regional distribution, with the caput epithelium being distinct from both the corpus and cauda, which are more similar (16). HNF1α and HNF1β protein levels in caput, corpus and cauda HEE cells were analyzed by western blot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Though in an analysis of gene expression in intact epididymis tissue segments by microarray (14), neither HNF1α nor HNF1β showed a regional distribution, this likely reflects the minor contribution of the epithelium to the whole tissue gene expression profile. We previously showed that HNF1β is much more abundant than HNF1α throughout the epididymis epithelium, though both show strong regional expression (16). Here, we confirm by western blot that HNF1β is much more abundant than HNF1α in caput HEE cells and so our data primarily relate to the functions of HNF1β.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations